# -0.6(3v-15)=0.4(3-5v)

## Simple and best practice solution for -0.6(3v-15)=0.4(3-5v) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -0.6(3v-15)=0.4(3-5v) equation:

Simplifying
-0.6(3v + -15) = 0.4(3 + -5v)
Reorder the terms:
-0.6(-15 + 3v) = 0.4(3 + -5v)
(-15 * -0.6 + 3v * -0.6) = 0.4(3 + -5v)
(9 + -1.8v) = 0.4(3 + -5v)
9 + -1.8v = (3 * 0.4 + -5v * 0.4)
9 + -1.8v = (1.2 + -2v)
Solving
9 + -1.8v = 1.2 + -2v
Solving for variable 'v'.
Move all terms containing v to the left, all other terms to the right.
Add '2v' to each side of the equation.
9 + -1.8v + 2v = 1.2 + -2v + 2v
Combine like terms: -1.8v + 2v = 0.2v
9 + 0.2v = 1.2 + -2v + 2v
Combine like terms: -2v + 2v = 0
9 + 0.2v = 1.2 + 0
9 + 0.2v = 1.2
Add '-9' to each side of the equation.
9 + -9 + 0.2v = 1.2 + -9
Combine like terms: 9 + -9 = 0
0 + 0.2v = 1.2 + -9
0.2v = 1.2 + -9
Combine like terms: 1.2 + -9 = -7.8
0.2v = -7.8
Divide each side by '0.2'.
v = -39
Simplifying
v = -39`